Chemical composition and biological activities of the essential oil from leaves of cleidion javanicum bl. - Sanseera D. (2017)
The essential oil from the leaves of Cleidion javanicum Bl. was isolated by hydrodistillation with the percentage yield of 0.003 % as a pale yellow liquid. The composition of the essential oil was analysed by means of GC-(FID) and GC-MS. Ten constituents accounting for 92.60% total oil were identified. The major components were ethyl linoleolate (32.12 %), hexadecanoic acid (26.77 %), trans-phytol (24.64 %) and iso-phytol (4.80 %). The antimicrobial, anticancer, antioxidant activities and cytotoxicity test of this essential oil were investigated. The oil showed non-cytotoxic effects against Vero cells (African green monky kidney) because it inhibited more than 50 % cell growth. The anticancer activity of the essential oil was performed using the Resazurin Microplate Assay (REMA). The oil showed anticancer activity against three cancerous human cell lines; KB-Oral Cavity Cancer, MCF7-Breast Cancer and NCI-H187-Small Cell Lung Cancer with the IC50 of 47.16 μgmL -1 , 40.23 μgmL -1 and 49.95 μgmL -1 respectively. The oil also showed antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa with the Minimum Inhibition Concentration (MIC) values of 25.00 mg/mL and 12.50 mg/mL respectively, using agar diffusion method. In addition, the essential oil also showed significant antioxidant activity with the IC 50 of 27.05 mg mL -1 by means of DPPH radical scavenging assay. © 2012, Copyright Har Krishan Bhalla & Sons.